2018
DOI: 10.33549/physiolres.933772
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Transcranial Magnetic Stimulation (rTMS) Modulates Hippocampal Structural Synaptic Plasticity in Rats

Abstract: Repetitive transcranial magnetic stimulation (rTMS) was shown to have therapeutic potential for some neurological and psychiatric disorders. Previous studies reported that low-frequency rTMS (</=1 Hz) affected synaptic plasticity in rats, however, there were few investigations to examine the possible effects of rTMS on structural synaptic plasticity changes in rats, which included the effects on synaptic morphology in the hippocampus, synaptic protein markers and Ca(2+)/calmodulin-dependent protein II (CaMK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 32 publications
(11 reference statements)
1
6
0
Order By: Relevance
“…Dendrites are highly dynamic structures and change their structure and complexity in response to the stimuli received [42]. According to this hypothesis, our results could represent a form of activity-dependent plasticity [43][44][45] and expand a previous finding indicating that LF rTMS treatment increased the hippocampal synapses density [46]. It is likely that these changes may affect the information processing at the circuit level, influencing, in this way, complex behaviors [47].…”
Section: Discussionsupporting
confidence: 81%
“…Dendrites are highly dynamic structures and change their structure and complexity in response to the stimuli received [42]. According to this hypothesis, our results could represent a form of activity-dependent plasticity [43][44][45] and expand a previous finding indicating that LF rTMS treatment increased the hippocampal synapses density [46]. It is likely that these changes may affect the information processing at the circuit level, influencing, in this way, complex behaviors [47].…”
Section: Discussionsupporting
confidence: 81%
“…High-frequency rTMS induces excitatory postsynaptic potential changes, resulting in the LTP effect. On the other hand, low-frequency rTMS induces inhibitory postsynaptic potential changes, leading to the LTD effect ( Li et al, 2019 ). Neuroimaging-based studies have demonstrated that high-frequency rTMS increases local cortical blood perfusion and moderates cholinergic neuron damage resulting from localized blood perfusion, thereby slowing the progression of cognitive dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that high-frequency rTMS can modulate both synaptic markers and neurotrophic factors, potentially promoting synaptic regeneration and functional recovery following brain injury [ 76 ]. Under non-pathological conditions, it has also been shown that rTMS (at 0.5 Hz 500 pulses per session) increased the level of synaptic density in the hippocampus and that these changes are mediated by CaMKII activity [ 77 ].…”
Section: Discussionmentioning
confidence: 99%